2007
DOI: 10.3844/ajessp.2007.43.53
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Landfill Leachate using Limestone/Sandstone Filters Under Aerobic Batch Conditions

Abstract: The suitability of a passive technology, consisting of filters composed of a mixture of limestone and sandstone rocks, for the treatment of landfill leachates containing 6.6 mg Lˉ1 iron and 1.8 mg Lˉ1 manganese were investigated. The limestone and the limestone/sandstone filters successfully removed iron from the prepared solutions. The filters removed on average a minimum of 97.60% of the iron from solution on a daily basis. The removal of manganese from solution was not as eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…5 and COD were 98% and 94%, respectively (14). While in our study, the average removal efficiencies of BOD 5 and COD were lower due to the presence of interfering matters in the leachate such as nitrogen compounds, volatile fatty acids, heavy metals, ammonium, toxic, and pharmaceutical substances which inhibit biological activity. Hajiabadi et al (2009) showed that COD removal efficiency was above 97% in treatment of strong synthetic wastewater in SBR reactor in different cell residence times (CRT).…”
Section: Cod Scod Rbcod and Bod5mentioning
confidence: 46%
See 4 more Smart Citations
“…5 and COD were 98% and 94%, respectively (14). While in our study, the average removal efficiencies of BOD 5 and COD were lower due to the presence of interfering matters in the leachate such as nitrogen compounds, volatile fatty acids, heavy metals, ammonium, toxic, and pharmaceutical substances which inhibit biological activity. Hajiabadi et al (2009) showed that COD removal efficiency was above 97% in treatment of strong synthetic wastewater in SBR reactor in different cell residence times (CRT).…”
Section: Cod Scod Rbcod and Bod5mentioning
confidence: 46%
“…The sludge from aeration basin of municipal wastewater treatment plant in the north of Isfahan was used for seeding the aerobic reactor. During this study, COD, SCOD, rbCOD, BOD 5 , TKN, and TP parameters were analyzed, while DO, pH, and temperature parameters were controlled.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations